Design of Two Feeder Three Phase Four Wire Distribution System Utilizing Multi Converter UPQC with Fuzzy Logic Controller - Chandra Babu Paduchuri; Subhransu Sekhar Dash; Subramani Chinnamuthu (Advances in Electrical and Electronic Engineering, 2014)
This paper proposes the instantaneous p-q theory based fuzzy logic controller (FLC) for multi converter unified power quality conditioner (MC-UPQC) to mitigate power quality issues in two feeders three-phase four-wire distribution systems. The proposed system is extended system of the existing one feeder three-phase four-wire distribution system, which is operated with UPQC. This system is employed with three voltage source converters, which are connected commonly to two feeder distribution systems. The performance of this proposed system used to compensate voltage sag, neutral current mitigation and compensation of voltage and current harmonics under linear and nonlinear load conditions. The neutral current flowing in series transformers is zero in the implementation of the proposed system. The simulation performance analysis is carried out using MATLAB.